1999
DOI: 10.1016/s0194-5998(99)70414-6
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea in Children with Achondroplasia: Surgical and Anesthetic Considerations

Abstract: Obstructive sleep apnea is very common in children with achondroplasia. Surgery is effective, but recurrent symptoms are common, particularly when the initial procedure is adenoidectomy. The complication rate is higher than that observed in a general pediatric population but is readily managed with standard therapy. Anesthesia can be given safely to these patients with special consideration for limited neck extension and appropriate endotracheal tube size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
1
2

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(62 citation statements)
references
References 31 publications
2
55
1
2
Order By: Relevance
“…Children with OSAS have increased frequency of interictal epileptiform discharges (class IV) [41]. g) Class III or IV studies have demonstrated a high prevalence of OSAS and central apnoeas in children with achondroplasia (midface hypoplasia and brainstem compression) [42][43][44]. Chiari malformation is accompanied by obstructive and central apnoeas and hypoventilation with risk factors being the degree of brainstem crowding at the foramen magnum and the length of herniation (class III-IV) [45][46][47][48].…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Children with OSAS have increased frequency of interictal epileptiform discharges (class IV) [41]. g) Class III or IV studies have demonstrated a high prevalence of OSAS and central apnoeas in children with achondroplasia (midface hypoplasia and brainstem compression) [42][43][44]. Chiari malformation is accompanied by obstructive and central apnoeas and hypoventilation with risk factors being the degree of brainstem crowding at the foramen magnum and the length of herniation (class III-IV) [45][46][47][48].…”
Section: Literature Reviewmentioning
confidence: 99%
“…b) AHI >4.7 episodes·h −1 and obesity are significant risk factors for residual OSAS post-adenotonsillectomy (class I and IV, and meta-analysis) [126,156,213]. Efficacy of adenotonsillectomy is modest in children with SDB and craniofacial abnormalities and/or neuromuscular disorders (class IV) [44,185,188,193,194,[214][215][216]. c) Quality of life improves post-adenotonsillectomy (class I and III, meta-analysis and systematic review) [111,113,126,178,211,217,218].…”
Section: Literature Reviewmentioning
confidence: 99%
“…While in the formers, SDB becomes clinically significant early, in achondroplasia, SDB usually develops in later years with a rate of at least 40%. Early occurrence does occur [33]. A study of 17 infants with achondroplasia and respiratory difficulties showed that in addition to the maxillary hypoplasia, "relative" adenotonsillar hypertrophy, muscular and neurological factors resulting from small foramen magnum, and hydrocephalus contributed to SDB [34].…”
Section: Craniofacial Malformationsmentioning
confidence: 99%
“…childhood [3,6,33]. A major difference between infants who are referred because of excessive night wakings and non-referred infants lies in the phenomenology of night wakings.…”
mentioning
confidence: 99%
“…Difficult airway features (Figure 1) are present due to the premature fusion of the skull base, frontal bossing, depressed nasal bridge, maxillary hypoplasia, macroglossia, abnormal teeth implantation, large mandible, short neck with fat deposition, cervical osteophytes and anomaly causing atlanto-axial instability and limited neck extension [1,3,4,5]. Foramen magnum is narrow and funnel shaped and can be compressed during laryngoscopy and cause cord ischemia leading to sudden death [4].…”
Section: Discussionmentioning
confidence: 99%